Periodontitis as a Risk Factor of Preeclampsia in Pregnancy: A Scoping Review - Ridho, Fiki Muhammad; Algifnita, Avina Oktaviani; Pramaztri, Naurah Nabilah; Laksono, Eko Puji; Allifiah, Bella Pardian Nur; Ahmad, Mahesa (Jurnal Medis Islam Internasional, 2024)
Introduction: Preeclampsia (PE) is a pregnancy complication characterized by hypertension and proteinuria after 20 weeks of gestation. Although the causes of PE are still unclear, there are factors that play an important role in increasing the incidence of PE, namely periodontitis which has an impact on the systemic spread of pathogens and inflammatory mediators, causing adverse pregnancy outcomes. This scoping review aims to evaluate, identify and provide a deeper understanding of the relationship and possible mechanisms between periodontitis and increased PE in pregnant women. A literature search following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines was conducted in PubMed, ScienceDirect, Scopus, and Google Scholar until July 2023. In the end, 14 articles were included for review. Results: All of the included studies stated that periodontitis mostly affects pregnant women with PE, and periodontitis is believed to play a role in increasing the risk of PE through the mechanism of bacteremia due to periodontal pathogens translocating from the oral cavity to the placenta and through cytokines and inflammatory mediators produced by inflamed periodontal tissue, resulting in disruption of the placenta, further increasing the risk of PE in pregnant women. Conclusions: In conclusion, there is a significant increase in the incidence of PE in pregnant women who experience periodontitis. Future research to review the mechanisms by which periodontitis increases the risk of PE and to examine whether periodontitis treatment before and during pregnancy can prevent PE may be warranted.